The remarkable life and times of Eliza Rose - Hooper, Mary, 1948- (New York : Bloomsbury, 2006)
Thrown out of her home by her stepmother in 1670, fifteen-year-old Eliza Rose becomes a companion to the Nell Gwyn, a mistress of Charles II, and learns a surprising truth about her parentage.
Keywords: Gwyn, Nell, -- 1650-1687 -- Juvenile fiction; Gwyn, Nell, -- 1650-1687 -- Fiction; Identity (Psychology) -- Juvenile fiction; Identity -- Fiction; London (England) -- History -- 17th century -- Juvenile fiction; Great Britain -- History -- Charles II, 1660-1685 -- Juvenile fiction; London (England) -- History -- Fiction; Great Britain -- History -- Fiction